2016
DOI: 10.1001/jamasurg.2015.4205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations and Molecular Variables of Primary Vascular Leiomyosarcoma

Abstract: Importance Vascular leiomyosarcomas (vLMS) are a rare subtype of leiomyosarcomas (LMS) most commonly affecting the inferior vena cava and accounting for 5% of all LMS. These tumors are aggressive malignancies for which adjuvant modalities have not shown increased efficacy compared over surgery. Our study evaluates potential molecular markers that should be evaluated in prospective studies to determine their prognostic and therapeutic utility. Objective To evaluate the outcomes of patients with vLMS and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
(39 reference statements)
2
41
0
Order By: Relevance
“…Time to recurrence was measured from the date of the treatment termination to first re-visit or to last follow-up. The recurrence rate was estimated using the Kaplan-Meier method, and difference of the recurrence rates between two groups was compared using the log-rank test 13 14 . Each variable which showed a significant difference between two groups was evaluated in the simple Cox proportional hazards model.…”
Section: Methodsmentioning
confidence: 99%
“…Time to recurrence was measured from the date of the treatment termination to first re-visit or to last follow-up. The recurrence rate was estimated using the Kaplan-Meier method, and difference of the recurrence rates between two groups was compared using the log-rank test 13 14 . Each variable which showed a significant difference between two groups was evaluated in the simple Cox proportional hazards model.…”
Section: Methodsmentioning
confidence: 99%
“…Development of LMS is characterized by the presence of complex and unbalanced karyotypes, resulting in genomic instability associated with multiple gene aberrations such as TP53, RB1, CDKN2A, IGFR, and PTEN [6,[29][30][31]. These gene aberrations subsequently cause the activations of corresponding signaling pathways such as the RB1/ cyclin D1, p53/MDM2, PI3K/AKT/mTOR, and IGFR/AKT pathways, which provided potential targets for future drug development [32][33][34][35].…”
Section: Potential Benefit Of Using Gene Aberrationrelated Therapy Fomentioning
confidence: 99%
“…LMS is relatively rare representing 10–20% of soft tissue sarcomas . It can appear at almost all anatomic sites such as the uterus , retroperitoneum , extremities , and blood vessels . Uterine LMS is the most common site‐specific group with an estimated incidence of 0.64 cases per 100,000 women .…”
Section: Introductionmentioning
confidence: 99%
“…The following expression levels were significantly higher in leiomyosarcomas than in PTSMT (Table 2 ): WNT9B, GAS1, signaling factor desert hedgehog (DHH), the two Notch signaling pathway factors LFNG O-fucosylpeptide 3-beta-N-acetylglucosaminyltransferase provided (LFNG) and MFNG O-fucosylpeptide 3-beta-N-acetylglucosaminyltransferase (MFNG), protein kinase cAMP-activated catalytic subunit alpha (PRKACA) and insulin-like growth factor 1 (IGF1). Roland et al [ 10 ] showed that leiomyosarcomas also express the IGF receptor which indicates paracrine activation.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that many canonical WNT signaling factors were not increased and that we found no nuclear beta-catenin indicates activation of the non-canonical WNT pathway. Similar to PTSMT, leiomyosarcomas usually show no aberrant nuclear beta-catenin expression [ 10 , 16 ]. Non-canonical WNT signaling is often characterized by alternative signaling without cytoplasmic stabilization of soluble beta-catenin [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%